IMPLEMENTASI PELAYANAN PUBLIK DALAM PENGURUSAN KARTU TANDA PENDUDUK ELEKTRONIK PADA KANTOR DINAS CATATAN SIPIL TANAH KARO - Sri Devi (SUAN PUBLISHER, 2024)
The implementation of public services in the management of electronic identity cards at the Tanah Karo Civil Registry Office has problems in the management of electronic identity cards (E-KTP) due to the many public complaints such as the slow processing of KTPs, delayed recording due to network disturbances when recording E-KTPs. This study aims to find out how the process of implementing public services issued by the government is expected to be able to provide good quality and quality services as expected by the community. This study used Edward III's theory of four indicators: communication, resources, disposition, bureaucratic structure and was carried out using a qualitative descriptive method, solved through observations, interviews, observations, observations and describing the situation based on facts, the informants consisted of five people